Studi Pengaruh Setting Rele Pengaman untuk Meminimalkan Gangguan Sympathetic Trip pada Penyulang Bunisari-Suwung - Astana Ady, I Komang Anom; Arjana, I Gede Dyana; Parta, Cok Gede Indra (Majalah Ilmiah Teknologi Elektro; Vol 15 No 2 (2016): (July - December) Majalah Ilmiah Teknologi Elektro, 2016)
Sympathetic Trip that happened in the electricity distribution system cause the healthy feeder distrupted because feel a disorder in feeder which affected by a disorder.A residual current that flows as a result of disruption of the one phase to ground on the Bunisari feeder as much as 183,9 A will be perceived by the same phase in the Suwung feeder which has a residual current of 196,9 A, that resulting in the accumulation of capacitive current as much as 380,8 A.The efforts obtained to prevent the Sympathetic trip back with ground fault relay setting as Iset = 25,72 A, tms = 0,11 SI with relay working time for 0,27 seconds and for Suwung feeder is obtained Iset = 24,59 A, tms  = 0,115 SI with relay working time for 0,286 seconds .
Keywords: Sistem proteksi, setting ground fault relay, Simpatitik Trip.